Dental and Oral Hygiene Pocket Guide to Improve Tooth Brushing Skills and Dental Hygiene Status of Children with Disabilities through Parental Assistance - Nanda Bupa Pratama; Lanny Hapsari Winnursita; Endah Aryati Eko Ningtyas (ABDIGI : JURNAL PENGABDIAN MASYARAKAT KESEHATAN GIGI, 2024)
The results of the Riset Kesehatan Dasar (RISKESDAS) in 2018 stated that oral health problems in the Indonesian population increased in 2018. In 2013, the percentage of the Indonesian population who had oral and dental problems was 25.9% and then increased in 2018 to 57.6%. Forced children are quite vulnerable to oral health problems. The poor state of the oral cavity is due to unsupervised brushing, other factors such as brushing techniques, motor skills and assistance that are still ignored. In addition, there is a lack of visualization to understand and master oral hygiene practice techniques. Brushing is a common way to clean teeth from plaque and other dental debris. Plaque that remains in the oral cavity is one of the local irritant factors that cause caries and gingivitis. Therefore, the Dental and Oral Health Pocketbook innovation was made to overcome problems related to the dental health maintenance behavior of children with disabilities through parental assistance. Some of the steps applied in this activity include the preparation, implementation, and evaluation stages. This activity involved 7 children with disabilities, each accompanied by their parents in the implementation process. As a result of this activity, it can be concluded that the Pocket Guide proved to be effective in helping children with disabilities understand and apply proper tooth brushing techniques. In addition to improving skills, the program also succeeded in raising awareness about the importance of maintaining oral health.Keyword : pocket guide; tooth brushing skills; dental hygiene status; children with disabilities